Determination of the theoretical stress concentration factor in structural flat plates with two holes subjected to bending loads (2018)
Numerous research works have studied the stress distribution in sections with geometric discontinuities and the relationship with the theoretical factor of stress concentration using the finite element method. These works have dealt with topics such as the influence of the length of pieces on the factor in rectangular orthotropic plates; The behavior of the stress concentration factor on short shafts with section changes under bending loads; The theoretical factor of stress concentration in flat parts subjected to tension with "U" grooves; The estimation of the theoretical stress concentration factor for a flat plate with two holes subjected to tension loads. Other studies have compared the stress distribution by applying three methods: elasticity theory, finite element analysis and experimental techniques. Results show that the finite element method is effective in solving the problem. The goal of this research is to determine the theoretical stress concentration factor for a flat plate with two holes subjected to bending applying the finite element method. The modeling of the plate, the application of the loads, the mesh generation and the simulation of the stress distribution were made using the software ANSYS® Workbench. Four holes with different sizes were worked and for each of them 10 different values of the distance between centers were taken. In this way the relationship between the factor , the size of the holes and the distance between centers was found. This information is of great importance for the design of mechanical elements that are under these conditions.